Two novel semi-quantum-reflection protocols applied in connected vehicle systems with blockchain. (September 2020) - Zhu, Hongfeng; Wang, Xueying; Chen, Chien-Ming; Kumari, Saru
Abstract: The increasing evolution of Internet of Vehicles (IoV) is bringing about a crucial challenge in information security, which is typically classified into network and large data storage security areas. A quantum cryptosystem is secure against cloning, and is thus immune to many types of traditional network attacks. Blockchain is a distributed ledger technology based on a game theory consensus, and has already shown significant advantages in terms of data security. In this study, a method to extend the use of quantum and blockchain technologies in the security of IoV is considered. Herein, we present a semi-quantum system with a blockchain architecture and provide two lightweight approaches for its application to IoV with unconditional security and a single round of completion. Moreover, with our two protocols, only two modular exponentiations are applied, and the remaining computations are hash or XOR operations, which can be ignored. The results of our study may provide a guide for future applications toward IoV in the era of quantum and blockchain technologies.